Development and Detection Experiment of Scanning Stage for High-throughput Gene Sequencer. Issue 1 (1st March 2023) - Zhao, Yanyan; Cao, Yue; Tan, Wenjun; Yang, Tianshi; Chen, Hao
Abstract: In order to meet the requirements of large stroke, high precision, and high acceleration step scanning imaging of the worktable of a high-throughput gene sequencer, a mechanical ultra-precision positioning platform is designed. The XY translation table has a significant impact on the fluxes and accuracy of gene sequencing detection. Using the finite element method to analyze the structural modal and obtain the first-order natural frequency; Then using the vibration test system and laser interferometer to test the first-order natural frequency and the repeat positioning accuracy of the XY translation table. The test results show that the first-order natural frequencies of the platform in X, y and Z directions are 175Hz, 111Hz and 191Hz respectively, which is much higher than the upper-frequency limit of 16.7Hz step scanning servo bandwidth. The two-way repeat positioning accuracy of XY translation table are ± 0.462 µ m and ± 0.429 µ m, meet ± 0.6 µm. So the scanning stage can meet the index requirements of a high-throughput gene sequencers under the specified working conditions, and the measured test data combined with the modal analysis model can provide a research basis for the optimal design of the subsequent platform.